Corridors without Borders in West Africa - Lebrand, Mathilde (World Bank, Washington, DC, 2021)
This paper estimates the welfare gains from upgrading several major regional corridors in West Africa. It uses a quantitative economic geography framework with trade within and across countries and mobility of people within countries to assess the economic impacts of the reduction in trade costs from road and border infrastructure investments. The findings show that the upgrade of Dakar-Lagos regional road corridor brings sizable economic benefits relative to investment costs, with a benefit-cost ratio estimated around 3. The economic benefits of road corridor upgrades are doubled and more widely spread when combined with measures to reduce current massive border delays. The benefits are negligible for Nigeria, but large for small fragile states (Guinea-Bissau, Liberia, and Sierra Leone). The gains are highest for corridors connecting large economies, and smaller and more fragile countries gain proportionally more from accessing larger markets. Finally, regional investments, including border time reduction policies, will reduce spatial inequality in the whole region but might increase inequality in some countries.